Numerical Analysis of Vibration Responses in High-Speed Railways considering Mud Pumping Defect - Ting Li; Qian Su; Kang Shao; Jie Liu (Shock and Vibration, 2019)
As a newly appeared defect under slab tracks in high-speed railways, mud pumping weakens the support ability of the subgrade to slab track, bringing about deviations on the vibration responses of the vehicle, slab track, and subgrade. Therefore, this paper proposes a vehicle-slab track-subgrade coupled model based on the multibody simulation principle and the finite element theory to highlight the influences of mud pumping defect. As an external excitation to this model, random track irregularity is considered. In order to simulate the mud pumping defect, the contact between the concrete base and subgrade is described as a spring-damper system. This model is validated by field test results and other simulation results, and a very good agreement is found. The vibration responses of the vehicle, slab track, and subgrade under different mud pumping lengths and train speeds are studied firstly. The deviations of vibration responses in high-speed railways induced by mud pumping are then obtained, and the limited mud pumping length is put forward finally to provide a recommendation for maintenance works of high-speed railways in practice.